Linezolid Administration to Critically Ill Patients: Intermittent or Continuous Infusion? A Systematic Literature Search and Review - Ligia-Ancuta Hui; Constantin Bodolea; Laurian Vlase; Elisabeta Ioana Hiriscau; Adina Popa (MDPI AG, 2022)
A judicious antibiotic therapy is one of the challenges in the therapy of critically ill patients with sepsis and septic shock. The pathophysiological changes in these patients significantly alter the antibiotic pharmacokinetics (PK) and pharmacodynamics (PD) with important consequences in reaching the therapeutic targets or the risk of side effects. The use of linezolid, an oxazolidinone antibiotic, in intensive care is such an example. The optimization of its therapeutic effects, administration in intermittent (II) or continuous infusion (CI) is gaining increased interest. In a systematic review of the main databases, we propose a detailed analysis of the main PK/PD determinants, their relationship with the clinical therapeutic response and the occurrence of adverse effects following II or CI of linezolid to different classes of critically ill patients or in Monte Carlo simulations.